The CORVET complex promotes tethering and fusion of Rab5/Vps21-positive membranes - Balderhaar, Henning J. kleine (National Academy of Sciences, 2013)
Membrane fusion along the endocytic pathway occurs in a sequence of tethering, docking, and fusion. At endosomes and vacuoles, the CORVET (class C core vacuole/endosome tethering) and HOPS (homotypic fusion and vacuole protein sorting) tethering complexes require their organelle-specific Rabs for localization and function. Until now, despite the absence of experimental evidence, it has been assumed that CORVET is a membrane-tethering factor. To test this theory and understand the mechanistic analogies with the HOPS complex, we set up an in vitro system, and establish CORVET as a bona-fide tether for Vps21-positive endosome/vacuole membranes. Purified CORVET binds to SNAREs and Rab5/Vps21-GTP. We then demonstrate that purified CORVET can specifically tether Vps21-positive membranes. Tethering via CORVET is dose-dependent, stimulated by the GEF Vps9, and inhibited by Msb3, the Vps21-GAP. Moreover, CORVET supports fusion of isolated membranes containing Vps21. In agreement with its role as a tether, overexpressed CORVET drives Vps21, but not the HOPS-specific Ypt7 into contact sites between vacuoles, which likely represent vacuole-associated endosomes. We therefore conclude that CORVET is a tethering complex that promotes fusion of Rab5-positive membranes and thus facilitates receptor down-regulation and recycling at the late endosome.